Bibliometric analysis of research relating to hypertension reported over the period 1997–2016. Issue 11 (November 2019) - Devos, Patrick; Menard, Joël
Abstract : Objective: Hypertension, a major cardiovascular risk factor, may reach a global prevalence of 1.56 billion by 2025. Much research has been conducted in this field, but few bibliometric studies have been performed. We aimed to analyse the changes in scientific output relating to hypertension over the past two decades. Methods: We analysed, via PubMed and Web of Science, the scientific output relating to hypertension from 1997 to 2016. Quantitative (number of publications) and citation (top 1 and 10%) analyses were performed for output globally and by major countries/regions, with a particular focus on the European Union. Results: In total, 100 789 articles relating to hypertension were identified in Web of Science. The number of publications increased by 52.7% (3989 in 1997, 6092 in 2016). Of the 100 789 articles, 38% had authors from the European Union, 32.1% had authors from the USA, and 26.7% had authors from Asia, with a marked increase in contributions from China over the period analysed. Articles appeared in more than 400 journals and were cited nearly 2 556 000 times. The relative weights of different research fields have also changed over time. Conclusion: Combined use of PubMed and Web of Science enabled robust bibliometric analysis of the studies into hypertension published in the period 1997–2016, including assessment of the contributions from major countries, particularly those in the European Union. This study also allowed us to validate our methodology, which could be used to evaluate research policies and to promote international cooperation. Abstract : Supplemental Digital Content is available in the text